East Jangha (wall) of the Kumbheshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
A closer view of the east jangha (wall) of the Kumbheshwar Mahadev Temple. The wall scheme is similar to the two north and south sides of the temple, with depictions of apsaras (celestial damsels), ascetics, and dancers on the intermediate and corner projections. The bhadra (central projection) has an image of Chamunda. The image of Chamunda is shown here portrayed with a skeletal body, six-handed, and a scorpion on her stomach. Below the image is a supine human figure. Except for a damaru (small two-headed drum) and a khatvanga (staff with a skull), the other attributes of the Goddess are broken.